A tale of sorcery... ebook - Colfer, Chris (Tale of Magic, 2021)
The thrilling third book in Chris Colfer's #1 New York Times bestselling A Tale of Magic... series   Brystal Evergreen is running out of time. It’s almost been a year since she made a deal with Death to find and destroy the Immortal in exchange for her life and she still hasn’t found a single clue about who or where the Immortal is. To make matters worse, something dark and malignant has risen from deep within the earth that threatens life as we know it.  To stop this new evil, the fairies and witches must work with all the kingdoms and territories, including the Righteous Brotherhood and their Army of the Dead. But is the threat more familiar than they expected? And why are a secretive group of Sorcerers convinced Xanthous Hayfield is connected to it?